Who's who in the pecking order? Aggression and 'normal violence' in the lives of girls and boys - Phillips, Coretta (The British journal of criminology, 2003)
Recent research has focused on the aggression and violence experienced by young people in local schools and neighbourhoods. Self-report bullying, victimization and offending studies have documented the pervasive nature of this violence in the lives of young people and the legitimacy that it has. This paper explores some emergent themes in this research that span different disciplines, also drawing heavily on the findings from a small, exploratory study of girls' violence. The discussion centres on the social context of aggression and violence, the functionality of such behaviour, and its normalization in adolescent life. The paper concludes by examining the implications of this body of work for theory, policy and practice